Optimal control and dynamics of human-to-human Lassa fever with early tracing of contacts and proper burial - Al-Shomrani, Mohammed M.; Yusuf, Abdullahi (Amer Inst Mathematical Sciences-Aims, 2025)
Lassa fever is a zoonotic viral disease that is contagious. In this research, a nonlinear deterministic mathematical model of human-to-human transmission of Lassa fever is formulated, which concentrates on the impact of early tracing of contacts and proper burial. The goal of this research was to assess the impact of tracing contacts and the proper burial of deceased individuals. We performed the test of the existence of equilibrium on the model. We computed control and basic reproduction numbers, R(c )and R-0, using the next-generation matrix approach, and we were able to prove the global stability of the disease-free equilibrium using the comparison method. We ascertained that the equilibrium is globally asymptotically stable if R-c <1. We also show the existence of an endemic equilibrium point, where a unique endemic equilibrium has been found. Regarding the global stability of the endemic equilibrium point, we are able to prove the stability of the endemic equilibrium point globally using the Goh-Volterra type of Lyapunov function, which shows that the endemic equilibrium point is globally asymptotically stable if R-c >1, with the condition that if the disease-induced death rates, the hospitalization rate of quarantined and untraced individuals, and the reversion rate of quarantined and traced individuals are all equals to zero. Numerical simulation suggests that, if the traced contact rate can be made high, it can help in controlling Lassa fever disease in society, which will also lead to a decline in infectious individuals in society. If the proper burial rate can be made almost perfect, it can help in controlling Lassa fever disease in society, which will lead to a decline in the number of infectious individuals in society. The optimal control plot shows that the campaign to increase personal hygiene and public knowledge of the actions that increase the risk of sickness is more effective in controlling Lassa fever.
Keywords: Lassa fever; tracing of contacts; proper burial; stability analysis; basic reproduction number; optimal control